SYSTOLIC ARRAY FOR REALIZATION OF DISCRETE WAVELET TRANSFORM (Journal of Engineering, 2007)
This paper introduce a new method for using a systolic array to perform the one, and two dimension discrete wavelet transform (1-D DWT, and 2-D DWT). The 1-D needs only a semi-systolic array for its realization. However, it was found that the 2- D method needs the combination of two types of semi-systolic array into one systolic array to achieve its implementation.